The Influence of Salesperson Attributes and Perceived Service Quality on Customer Attitudes and Service Intentions in the Banking Sector - Suksudach, Sikarwit; Simakgahirnboon, Panuschagone (วารสารศิลปการจัดการ, 2026)
This study investigates the joint influence of salesperson attributes and perceived service quality on customer attitudes and service intentions in a commercial banking context, and examines the mediating role of customer attitude within a three-layer structural model informed by the Theory of Planned Behavior (TPB; Ajzen, 1991)—operationalizing its attitudinal component only—and by the SERVQUAL framework (Parasuraman, Zeithaml, & Berry, 1988). Design/methodology/approach: Data were collected from 391 customers of a commercial bank operating across five provinces in Thailand’s lower central region, stratified equally across loan, wealth-management, and basic-service segments. Partial least squares structural equation modeling (PLS-SEM) was conducted in SmartPLS 4.0 (Ringle, Wende, & Becker, 2022) with 5,000-subsample bias-corrected bootstrapping (Chin, 1998). Findings: Four of five directional hypotheses were supported. Salesperson attributes positively influenced customer attitude (β = .392, t = 8.412, p < .001, f² = .289) but exerted no significant direct effect on service intention (H2 not supported). Perceived service quality positively influenced both customer attitude (β = .315, t = 6.843, p < .001, f² = .251) and service intention (β = .373, t = 8.125, p < .001, f² = .295). Customer attitude emerged as the dominant path in the model (β = .441, t = 9.723, p < .001, f² = .313). Mediation analysis revealed a differential pattern: attitude fully mediated the salesperson attributes–service intention pathway (indirect β = .173, 95% CI [.112, .243]), while only partially mediating the perceived service quality–service intention pathway (indirect β = .139, 95% CI [.085, .201]; direct β = .373; total β = .512). Research limitations/implications: The measurement model exhibits significant discriminant validity limitations, including an HTMT ratio of 1.026 between the two antecedent constructs, which renders causal inferences provisional. The sample derives from a single bank in one Thai region and skews toward high-income, middle-aged business owners. All findings should therefore be treated as preliminary. Originality/value: The study’s most robustly supported contribution is a measurement one: in this premium Thai banking context, interpersonal salesperson attributes and technical service quality could not be empirically separated (HTMT = 1.026), indicating that customers may evaluate both as facets of a single service-encounter quality. Conditional on that boundary, the data are consistent with a differential mediation pattern in which interpersonal attributes reach behavioral intention only through attitude while service quality also operates directly—a pattern requiring replication with a re-specified instrument before it can be treated as an established finding.